Using radioisotope to study the dimethoate degradation capacity of bacteria - Le Ha, Pham Thi; Thuy, Tran Thi; Hang, Nguyen Duy (Academia Journal of Biology, 2014)
The dimethoate (Di) biodegradation capacity of 2 bacterium strains Aerococcus sp.T and Neiseria sp.C isolated from agricultural soil of Dalat city was determined by using 32P labeled dimethoate (32P-Di). Adding 32P-Di into the culture medium of these 2 bacterium strains, 32P-Di was quickly biodegraded and at 72 hours of cultivation, 32P-Di was not detected. After 120 hours of incubation, the radioactivity of 32P was mostly accumulated in the medium, partly in the biomass of bacteria. Intermediates found in the biotransformation processes by the strains Aerococcus sp.T and Neiseria sp.C were less than compared to the non biotransformation process and the poisonous intermediates were not found.